Enhancing Pre-Service English Teachers’ Professional Competence Through School-Based Practicum - Tanzilla Artikova (Indonesian Journal Publisher, 2025)
This study investigates the impact of school-based practicum on the development of professional competence among pre-service English language teachers. Conducted with 42 fourth-year undergraduate students enrolled in a TEFL program at Namangan State Institute of Foreign Languages, the research adopted a mixed-methods design involving pre- and post-practicum surveys, mentor evaluations, and reflective journals. Findings suggest that school-based practicum significantly enhances pedagogical skills, classroom management, language use, and reflective thinking. The study emphasizes the importance of structured mentoring and school-university collaboration in supporting pre-service teachers’ transition from theory to practice